Psychogeographical Remapping of Hong Kong between Being and Non-being in Liu Yichang’s Intersection - Su, Jianbo; Shanthini , Pillai (SARE: Southeast Asian Review of English, 2024)
Much has been done on positioning Hong Kong’s cultural impasse in the confrontation between the recent rise of Hong Kong nativism laced with pre-colonial lingering and the increasing force of nationalism from the mainland since its 1997 handover. However, overemphasis on the in-betweenness would incite a defensive mechanism for over-reactive self-justification and lead to the trap of radical nativism and intra-racial rivalry. Under this circumstance, this paper, inspired by the framework of psychogeography and Chinese Zen Daoism, proposes an innovative model that critically integrates dérive with being and non-being. This synergistic paradigm offers an alternative lens to reversely harness ambivalence and rootlessness as a tactical breakthrough in rereading Hong Kong’s hybridity in Liu Yichang’s Intersection as an imaginary space of multi-directional self-articulation. In addition, it contributes to actualizing a creative praxis of strategic intervention to disrupt the vicious circle of identity wrestling and anticipate a dialectical re-entry into the Hong Kong-Mainland identity landscape as a divergent yet interwoven duet.